Diversity and seasonal fluctuation of thrips species on yellow tree lupin (Lupinus arboreus) - He, S.; Nielsen, M-C.; Fagan, L.L. (New Zealand Plant Protection, 2009)
Yellow tree lupin (Lupinus arboreus) an abundant weed in New Zealand is host to several economically important thrips species The diversity and relative abundance of thrips found on yellow tree lupin were measured weekly via handcollections over the 2008/09 summer at two locations in Canterbury separated by 8 km From the 1540 thrips that were collected and slidemounted eight thrips species were identified The most abundant species was New Zealand flower thrips (Thrips obscuratus) followed by onion thrips (Thrips tabaci) the lupin strain of western flower thrips (Frankliniella occidentalis) Thrips vulgatissimus Thrips australis Limothrips cerealium Chirothrips manicatus and Tenothrips frici The largest variation in relative abundance occurred in early December with onion thrips dominant at Killinchy and western 64258;ower thrips dominant at Rakaia In late December at Rakaia the dominant species shifted to New Zealand 64258;ower thrips This indicates considerable spatial and temporal variation in relative abundance of thrips species